Freight Transportation Activity, Business Cycles and Trend Growth - Fredrik N. G. Andersson; Thomas Elger (Lund University, School of Economics and Management, Department of Economics, 2007)
This paper studies empirical linkages between cycles and trends in freight transportation activity and real economic activity in Sweden. We find that cycles in freight transportation are highly contemporaneously correlated with cycles in economic variables over both the short run and the medium run. The pattern of long run growth in freight transportation activity coincides with growth in economic variables during long periods, but there are also periods with substantial differences. Furthermore, we observe and explain a large decline in trend growth in tonne-kilometres by road from the mid-nineties and onwards.
Keywords: C19; E29; L92; 330; freight transportation; business cycles; trend growth; decoupling; efficiency